Growth Influence Mindset and Digital Literacy on Professional Teacher Work Motivation Through Resilience in High School - Mardiana, Ainun; Najamuddin, Najamuddin; Ibrahim , Ibrahim (Jurnal Paedagogy, 2025)
This study aims to analyze the influence of growth mindset and digital literacy on professional teacher work motivation with resilience as a mediating variable in public senior high schools in Jeneponto Regency, South Sulawesi Province. This study employed an ex-post facto quantitative approach with a sample of 104 teachers selected using a proportional sampling technique. The instrument used was a questionnaire with a Likert scale of 1–5, which consisted of indicators from four research variables: growth mindset, digital literacy, resilience, and teacher work motivation. Data analysis was conducted using descriptive and inferential analysis through validity and reliability tests, as well as hypothesis testing. The results indicate that growth mindset significantly influences work motivation (t-statistic = 2.672, p-value = 0.004) and resilience (t-statistic = 4.200, p-value = 0.000). Digital literacy also significantly influences work motivation (t-statistic = 3.118, p-value = 0.001) and resilience (t-statistic = 3.431, p-value = 0.000). Additionally, resilience plays a significant role in work motivation (t-statistic = 4.547, p-value = 0.000). Mediation tests prove that resilience mediates the effect of growth mindset (t-statistic = 3.372, p-value = 0.000) and digital literacy (t-statistic = 2.677, p-value = 0.004) on work motivation. The R-square value of 0.686 indicates that 68.6% of the variation in work motivation is explained by the research model.